Impaired health-related quality of life, psychological distress, and productivity loss in younger people with persistent shoulder pain: a cross-sectional analysis. Issue 15 (17th July 2022) - Ackerman, Ilana N.; Fotis, Kathy; Pearson, Lauren; Schoch, Peter; Broughton, Nigel; Brennan-Olsen, Sharon L.; Bucknill, Andrew; Cross, Emily; Bunting-Frame, Nicola; Page, Richard S.
Abstract: Purpose: To investigate wellbeing and work impacts in younger people with persistent shoulder pain. Materials and methods: People aged 20–55 years with shoulder pain of >6 weeks' duration (excluding those with recent fracture or dislocation) were recruited from orthopaedic clinics at three major public hospitals. Health-related quality of life (HRQoL) and psychological distress were evaluated using the Assessment of Quality of Life (AQoL) and K10 instruments and compared to population norms. Shoulder-related absenteeism and presenteeism were quantified using the Work Productivity and Activity Impairment (WPAI) Questionnaire. Results: Of the 81 participants (54% male), 69% had shoulder pain for over 12 months. Substantial HRQoL impairment was evident (mean reduction from population norms 0.33 AQoL units, 95% CI −0.38 to −0.27; minimal important difference 0.06 AQoL units). High or very high psychological distress was three times more prevalent among participants than the general population (relative risk 3.67, 95% CI 2.94 to 4.59). One-quarter of participants had ceased paid employment due to shoulder pain and 77% reported shoulder-related impairment at work. Conclusions: The broader impacts of painful shoulder conditions on younger people extend well beyond pain and upper limb functional limitations. In particular, the work-related impacts should form a routine part of patient assessment and rehabilitation. Implications for rehabilitation: Persistent shoulder pain in younger people (aged 20–55 years) is associated with substantially reduced health-related quality of life and greater psychological distress, compared to population norms, as well as work participation and productivity impacts. As rotator cuff conditions, shoulder capsule pathology, and glenohumeral instability are relatively common, our data suggest that persistent shoulder pain is likely to have a high community impact among people of working age. Information resources that people with painful shoulder conditions can share with their families, employers, and colleagues may assist others to better understand the broader impacts of these conditions. Work-related challenges associated with shoulder pain should be considered within routine clinical care, and may require referral to an occupational health clinician or vocational rehabilitation service.